Sistemi adesivi con applicazioni in campo biomedicale - Cordischi, Fabrizio <1982> (Alma Mater Studiorum - Università di Bologna, 2011)
Polymeric adhesives have been used for many applications like suture and embolization, instead of classic surgical methods or as for dental uses. In this work both subjects have been investigated and the results separated in two parts. In the first, new dentinal adhesives with different polymerizable groups (methacrylic or vinyl-ethereal) were synthesized. A low sensitivity to hydrolysis and equal or enhanced properties, compared to existing commercial products, were considered essentials. Moreover, these monomers need to polymerize by radical photopolymerization and functional groups of different characteristics were tested. All these products were characterized by microtensile bond strength test to determine the bonding strength between the adhesive and tooth. Concerning embolization, cyanoacrylates are nowadays the most-used adhesives in surgery. Thus, they must respond to several requirements. For instance, polymerization time and adhesive strength need to be low, to avoid diffusion of the products in the body and adhesion to the catheter. In order to overcome these problems we developed new cyanoacrylates, which practically instantly polymerize upon contact with blood but do not demonstrate strong adhesion to the catheter, thank to the presence of fluorine atoms, linked to the ester chain. The synthesis of these products was carried out in several steps, such as the depolymerization of the corresponding oligomers at high temperature in acid conditions. Two types of adhesion strengths were determined. Bonding strength between human veins and a microcatheter was determined in vitro by using organic materials as the most realistic model. Another test, on two layers of skin, was conducted to verify the possible use of these new cyanoacrylates as a glue for sutures. As a conclusion, we were able to demonstrate that some of the prepared monomers posses adhesive strength and polymerization time lower than the commercial product Glubran2.